1978
DOI: 10.1080/00222895.1978.10735144
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Processing and the Coding of Position Cues in Motor Short-Term Memory

Abstract: The present study investigated the appropriateness of the levels-of-processing framework of memory for explaining retention of information in motor short-term memory. Subjects were given labels descriptive of the positions to be remembered by the experimenter (EL), were given no labels (NL), or provided their own labels (SL). A control group (CONT) was required to count backwards during the presentation of the criterion positions. The inclusion of a 30-sec filled retention interval as well as 0-sec and 30-sec … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1978
1978
2003
2003

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The data were analyzed using a 2-factor MANOVAbased repeated-measures design with peak vertical GRF (expressed as a multiple of BW for each subject) as the dependent measure. The factors were treatment condition (instruction versus control) and sessions (1)(2)(3)(4)(5). It is common practice to use MANOVA rather than ANOVA procedures in repeated-measure designs because the former reduces the problem associated with violations of sphericity.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The data were analyzed using a 2-factor MANOVAbased repeated-measures design with peak vertical GRF (expressed as a multiple of BW for each subject) as the dependent measure. The factors were treatment condition (instruction versus control) and sessions (1)(2)(3)(4)(5). It is common practice to use MANOVA rather than ANOVA procedures in repeated-measure designs because the former reduces the problem associated with violations of sphericity.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…In addition, 7-year-old children are capable of using verbal rehearsal to analyze and label position cues in movement. 5,7 This evidence, taken together, suggests that children as young as 7 years of age should be ready to use verbal instruction to reduce GRFs during landing from a jumping task.…”
mentioning
confidence: 99%
“…Different encoding instructions, which can be considered as similar to instructions in the use of various strategies, have led to differences in memory performance based on the meaningfulness of the processing. An essentially identical finding has been reported when a motor task was used as the skill to be learned (Ho & Shea, 1978;Shea, 1977 A third question pertains to the underlying processes associated with strategy usage and skill learning.…”
Section: Acquisition Retention and Transfer Of Strategies And Rulesmentioning
confidence: 57%
“…An Brown, 1974) and motor skills (Hagenbeck, 1978;Ho & Shea, 1978;Shea, 1977), but the generalizability (transfer) of the strategies to other situational contexts has not been thoroughly investigated.…”
Section: Facilitating Acquisitionmentioning
confidence: 99%
“…Of particular concern in this study is the development of semantic codes (labels) involving relations. 1 A number of studies have shown that labeling increases both cognitive and motor performance and that the increase is relative to the meaningfulness ofthe label (Ho & Shea, 1978;Klatzky & Rafnel, 1976;Shea, 1977). Three groups used either meaningful, nonsense, or no label for cued and free recall with nonsense pictures (Kiatzky & Rafnel, 1976).…”
mentioning
confidence: 98%